BUDIDAYA TANAMAN MAHONI (Sweitenia macrophylla) DAN PEMANFAATANNYA SEBAGAI TANAMAN OBAT - AA Komang Suardana (UNHI Press, 2018)
Batukau Mount with its dense forest as the lungs of Tabanan Regency. As a buffer zone, water sources can irrigate existing subak, one of them is Jatiluwih Subak which is a World Cultural Heritage. At the south foothill of Mount Batukau Mount there is Sad Kahyangan Temple, Batukau Temple. Nature preservation around the temple is still maintained, but over time there are areas that need to be greened. Based on this situation, community service around Batukau Temple is carried out with the theme